Menopause in the workplace: What employers should be doing. (March 2016) - Jack, Gavin; Riach, Kathleen; Bariola, Emily; Pitts, Marian; Schapper, Jan; Sarrel, Philip
Abstract: Large numbers of women transition through menopause whilst in paid employment. Symptoms associated with menopause may cause difficulties for working women, especially if untreated, yet employers are practically silent on this potentially costly issue. This review summarises existing research on the underexplored topic of menopause in the workplace, and synthesises recommendations for employers. Longstanding scholarly interest in the relationship between employment status and symptom reporting typically (but not consistently) shows that women in paid employment (and in specific occupations) report fewer and less severe symptoms than those who are unemployed. Recent studies more systematically focused on the effects of menopausal symptoms on work are typically cross-sectional self-report surveys, with a small number of qualitative studies. Though several papers established that vasomotor (and associated) symptoms have a negative impact on women's productivity, capacity to work and work experience, this is not a uniform finding. Psychological and other somatic symptoms associated with menopause can have a relatively greater negative influence. Physical (e.g., workplace temperature and design) and psychosocial (e.g., work stress, perceptions of control/autonomy) workplace factors have been found to influence the relationship between symptoms and work. Principal recommendations for employers to best support menopausal women as part of a holistic approach to employee health and well-being include risk assessments to make suitable adjustments to the physical and psychosocial work environment, provision of information and support, and training for line managers. Limitations of prior studies, and directions for future research are presented.